PENGGUNAAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM BERWAWASAN LINGKUNGAN DALAM MENUMBUHKAN LITERASI EKOLOGI PADA SISWA SEKOLAH MENENGAH PERTAMA - Rahmat, Hayatul Khairul; Affandi, Akhmad (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to describe the use of environmentally oriented Islamic Religious Education (PAI) teaching materials in fostering ecological literacy among students at State Junior High School 32 in Tangerang City. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that integrating Islamic environmental values into PAI materials positively influences students' understanding, awareness, and behavior toward ecological issues. Teachers actively apply innovative project-based learning methods focusing on environmental topics such as waste management and school greening. Additionally, parental and community involvement play a crucial role in supporting students' ecological literacy development. Nevertheless, challenges remain, including limited environmental resources and infrastructure in schools. The study recommends strengthening the curriculum, enhancing teacher training, and fostering multi-stakeholder collaboration to reinforce environmentally conscious education.